Determination of Pharmacokinetics and Withdrawal time of Enrofloxacine Antibiotic on Catfish (Clarias gariepinus) - Mustahal Mustahal; Dina Solihah; Forcep Rio Indaryanto; Niezha Eka Putri (JURNAL PERIKANAN DAN KELAUTAN, 2020)
The purpose of this study was to determine the pharmacokinetics and time of withdrawal of antibiotic enrofloxacin in catfish (Clarias gariepinus) which was attacked by Aeromonas hydrophila. The study was conducted from June to August 2017 at Station for Investigation of Fish Health and Environment, at Pasauran, Serang Regency. The experimental method consisted of two treatments and three replications with each container using 110 fishes. Control treatment was those without antibiotics, while the withdrawal time was those with antibiotics during five days, after five days the withdrawal time container was without antibiotics again. The pharmacokinetics and withdrawal time were determined by the longest time in the organ (ELISA method) and water quality were analyzed descriptively. Data analysis using 95% confidence interval and 50% confidence interval MRL (limited residual maximum). The results showed that the catfish antibiotic was found highest in the renal organ were 360.73 μg / kg before the renal treatment of 10.68 μg / kg and the liver after the highest treatment was 415.75 μg / kg before liver treatment 13.60 μg / kg and increased after treatment. Therefore, the withdrawal time of antibiotic enrofloxacin in catfish was at 16 days.